2022
DOI: 10.1108/ijlm-02-2021-0121
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the whole systems approach: designing supply chains in a turbulent world

Abstract: PurposeThe systems approach is an exemplar of design science research (DSR), whereby specific designs yield generic knowledge. DSR is increasingly being adopted in logistics and operations management research, but many point to neglect of the human aspects of solutions developed. The authors argue that it is possible to look back at the history of the systems movement to seek precedent for ‘dealing’ with the social components, providing a methodologically pluralistic ‘research design’ framework. Thereby, syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…Figure 1 provides examples for each domain in the context of projects and interpreted in an operations management setting [36]. There is also a fifth domain (Disorder), for when there is ambiguity from decision maker(s) as to which of the other four domains their operational context resides within.…”
Section: B Decision-making and The Cynefin Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 provides examples for each domain in the context of projects and interpreted in an operations management setting [36]. There is also a fifth domain (Disorder), for when there is ambiguity from decision maker(s) as to which of the other four domains their operational context resides within.…”
Section: B Decision-making and The Cynefin Frameworkmentioning
confidence: 99%
“…adapted from [33] From its origins in knowledge management [32]- [33], the Cynefin framework has been extended to management leadership [34], and more recently exploited in various operations management contexts, including healthcare [37] procurement [60], performance alignment [38], project management [39], supply chain design [36], and construction management [40]. Naim, Gosling and Hewlett undertook a comprehensive risk analysis of the failures in an infrastructure project.…”
Section: Fig 1 Cynefin Representation With Key Characteristicsmentioning
confidence: 99%
“…After preliminary research, we found those systems-based approaches are widely used in both fields, hence potentially providing a bridge for knowledge sharing between Project Management (PM) and Supply Chain Management (SCM). While we focus on the quantitative SD and CT techniques the models developed from empirical studies are often founded on qualitative systems approaches such as systems thinking and soft system methodology (Naim and Gosling 2022) but such methods are beyond the scope of this study.…”
Section: Materials Collection and Analysis Processmentioning
confidence: 99%